The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0104-66321997000400008
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Catalysis by Permeabilized Cells

Abstract: This paper presents an enzymatic process for sorbitol and gluconic acid production using cells of Zymomonas mobilis permeabilized with CTAB. Equimolar solutions of glucose and fructose (from 96.0 to 422.2 g/L) were used. In a batch reactor, conversions of 97% were attained after 15 to 20 hours of reaction. The effect of the initial concentration of the substrates was evaluated in experiments using 20% more and 20% less glucose than fructose. It was observed that the reaction performed with more fructose reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Consequently, we concluded that the quantification of enzyme activity based on rates of hydroxide consumption is very reliable, as described and recommended by several authors [9,10,19,22]. In addition, preliminary tests carried out by our group with standard solutions prepared with known enzyme compositions indicated that the precision of reaction rate measurements was better than 1.0 9 10 -4 g l -1 h -1 , which is much lower than the precision reported here when distinct fermentation runs and reaction tests were performed.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Consequently, we concluded that the quantification of enzyme activity based on rates of hydroxide consumption is very reliable, as described and recommended by several authors [9,10,19,22]. In addition, preliminary tests carried out by our group with standard solutions prepared with known enzyme compositions indicated that the precision of reaction rate measurements was better than 1.0 9 10 -4 g l -1 h -1 , which is much lower than the precision reported here when distinct fermentation runs and reaction tests were performed.…”
Section: Resultssupporting
confidence: 57%
“…As the reaction between glucose and fructose is equimolar, the use of the hydroxide mass consumed during the reaction to estimate the concentration of all reagents and products has been well documented [9,10,19,22]. In order to check if this assumption remains valid for the reaction of fructose and lactose, we used a second, independent methodology to quantify lactose, as described in the previous section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chemical Engineering Program’s Bioprocesses Laboratory at COPPE, Federal University of Rio de Janeiro, Brazil, has used the bacterium Zymomonas mobilis for years to study the production of various substances, like ethanol, glyconic acid, sorbitol, lactobionic acid, and L-asparaginase [ 11 16 ]. The L-asparaginase obtained from Z .…”
Section: Introductionmentioning
confidence: 99%